Survey on Panama Wilt Disease (Fusarium oxysporum f.sp. cubense) of Banana in Mysuru, Mandya and Chamarajanagar Districts of Karnataka - Archith, T. C.; Devappa, V.; Mesta, R. K.; Honnabyraiah, M. K.; Rudresh, D. L. (International Journal of Economic Plants, 2021)
The roving survey was carried to find out the prevalence of Fusarium wilt disease incidence in banana cultivars during 2016-17 to 2017-18 in different places of Mysuru, Mandya and Chamarajanagar districts of Karnataka. During the survey, the average disease incidence of Fusarium wilt was ranged from 6.54 to 25.47%. The mean disease incidence in Mysuru district was 15.00% during 2016-17 and 25.47% in 2017-18, Mandya district recorded the average disease incidence of 6.54% during 2016-17 and 7.88% in 2017-18 and Chamarajanagar district showed the average disease incidence of 13.24% during 2016-17 and 10.56% in 2017-18. Among districts, Mysuru recorded the highest average disease incidence followed by Chamarajanagar. While the severe form of disease was observed in the cultivar Nanjanagudu Rasabale (60.57%) in Krishnapura village of Nanjangud taluk. However, among all the locations surveyed the highest disease incidence recorded was 60.57 % and lowest incidence was 0.00%. The maximum wilt incidence (%) was recorded in cultivar Nanjangud Rasabale followed by Ney Poovan 28.00 %. Nanjangud taluk of Mysuru district reported severe incidence level of panama wilt disease when compared to other taluks and districts. The wilt incidence (%) was higher during 2017-18 showing the consecutive increase in the disease incidence compare to 2016-17. The increased wilt incidence (%) was due to virulence of the pathogen and susceptibility of the cultivars.